Food‐symptom diaries can generate personalized lifestyle advice for managing gastrointestinal symptoms: A pilot study. Issue 8 (7th February 2020) - Clevers, Egbert; Nordqvist, Alex; Törnblom, Hans; Tack, Jan; Masclee, Ad; Keszthelyi, Daniel; Van Oudenhove, Lukas; Simrén, Magnus
Abstract: Background: Gastrointestinal (GI) symptoms have a heterogeneous pathophysiology. Yet, clinical management uses group‐level strategies. There is a need for studies exploring personalized management options in patients with GI symptoms. From diaries of GI symptoms, food intake, and psychological distress, we extracted and validated personalized lifestyle advice. Secondly, we investigated group‐level GI symptom triggers using meta‐analysis. Methods: We collected 209 diaries of GI symptoms, food intake, and psychological distress, coming from 3 cohorts of patients with GI symptoms (n = 20, 26, and 163, median lengths 24, 17, and 38 days). Diaries were split into training and test data, analyzed, and the triggers emerging from the training data were tested in the test data. In addition, we did a random effects meta‐analysis on the full data to establish the most common GI symptom triggers. Key Results: Analysis of the training data allowed us to predict symptom triggers in the test data (r = 0.27, P  < .001), especially in the subset of patients with a strong global association between lifestyle factors and symptoms (r = 0.45, P  < .001). Low exposure to these triggers in the test data was associated with symptom reduction ( P  = .043). Meta‐analysis showed that caloric intake in the late evening or night predicted an increase in GI symptoms, especially bloating. Several food‐symptom associations were found, whereas psychological distress did not clearly lead to more severe GI symptoms. Conclusions & Inferences: Diaries of GI symptoms, food intake, and psychological distress can lead to meaningful personalized lifestyle advice in subsets of patients. Abstract : For patients with gastrointestinal symptoms, there is a need to identify any person‐specific lifestyle factors that may trigger their symptoms. One approach would be for a patient to keep a diary of food intake, psychological distress, and gastrointestinal symptoms. Such diaries can be analysed using an in‐house developed algorithm. We provide evidence that this 'diary approach' can generate person‐specific lifestyle advice for managing gastrointestinal symptoms..